Africa Adaptation Atlas Hazards - NexGDDP CMIP6 - Achicanoy Estrella, Harold Armando; Ramirez Villegas, Julian Armando; Rosenstock, Todd Stuart; Steward, Peter Richard; Youngberg, Brayden; Castro Llanos, Fabio Alexander (2025)
The Adaptation Atlas NexGDDP hazards dataset provides 0.25° resolution historical and future climate-related hazard indicators derived from the NASA NexGDDP CMIP6 projections. The dataset covers 4 Shared Socioeconomic Pathways (SSP1-2.6, SSP2-4.5, SSP3-7.0, SSP5-8.5) and four future periods between 2021 and 2100, based on 18 global climate models (ACCESS-CM2, ACCESS-ESM1-5, CMCC-ESM2, CanESM5, EC-Earth3, EC-Earth3-Veg-LR, GFDL-ESM4, INM-CM4-8, INM-CM5-0, IPSL-CM6A-LR, KACE-1-0-G, MIROC6, MPI-ESM1-2-HR, MPI-ESM1-2-LR, MRI-ESM2-0, NorESM2-LM, NorESM2-MM, TaiESM1) and their multi-model ensemble mean. Using daily projections of temperature, precipitation, solar radiation, and relative humidity, the dataset includes ten hazard indices spanning drought stress, heat stress for crops, humans, and livestock, and waterlogging and flooding conditions.